Oxidative Stress Markers in Patients with Metabolic Syndrome - Axana Rodríguez Núñez; Jorge Calá Fernández; Haydee Cruz Vadell; Miguel Ángel Montoya Deler (Universidad de las Ciencias Médicas de Cienfuegos, 2021)
Background: oxidative stress is the balance alteration existing in the body between the action of oxidizing agents. Oxidative stress plays an important role in the pathogenesis of the metabolic syndrome because it affects the function of pancreatic beta cells and alters glucose transport in muscle and adipose tissue. Objective: to characterize a population with a metabolic syndrome diagnosis, according to biochemical and anthropometric variables between 2015-2016. Methods: a descriptive and cross-sectional study was carried out in patients with a diagnosis of metabolic syndrome belonging to the Julián Grimau and Carlos Juan Finlay health areas of Santiago de Cuba, in the period between 2015-2016. The variables analyzed were: age, sex, presence of arterial hypertension, triacylglycerides, glycemia, anthropometric variables, levels of oxidative markers for protein and lipids, defense marker against oxidative stress. The sample of 119 patients, obtained through simple random sampling. Data processing was performed using SPSS 20.0. For statistical tests, a p <0.05 and a 95 % confidence level were used. Results: the age groups of 60 to 69 years, female sex, overweight and hypertensive patients predominated in the study patients, in addition to altered levels of abdominal circumference, glycemia, triglycerides, HDL-C. Conclusions: oxidative stress appear in a remarkable way in these patients, with a significant increase in metabolites product of molecular oxidation and decrease in antioxidant systems in relation to the reference values, for which a statistically significant difference was found between these values.